Study on Reservoir Characteristics and Main Controlling Factors of Chang-7 Reservoir in the Southwest of Wuqi Oilfield - Ma, Xiong; Yin, Lu; Zhou, Ping (Scientific Journal of Technology, 2025)
This paper focuses on the problems of unclear oil and gas enrichment laws and difficult prediction of favorable zones in the tight reservoir of the Chang-7 member in the southwest of Wuqi Oilfield. It conducts research on reservoir characteristics and main controlling factors to provide a geological basis for efficient exploration in this area. By comprehensively applying technical methods such as detailed core observation, cast thin sections, scanning electron microscopy, high-pressure mercury intrusion, and basin simulation, the petrology, pore structure, and physical properties of the reservoir are systematically analyzed, and the controlling mechanisms of tectonism, sedimentation, and diagenesis are deeply discussed. The results show that the Chang-7 reservoir in the study area is an ultra-low porosity and ultra-low permeability lithic arkose sandstone, with intergranular pores and feldspar dissolution pores as the main pore types. The reservoir quality is controlled by multiple factors: sedimentary facies zones control the distribution of high-quality reservoirs such as sandy debris flows and turbidite sand bodies; in diagenesis, strong compaction and cementation lead to reservoir densification, while dissolution effectively improves the reservoir space; most importantly, the tectonic uplift and denudation since the Late Cretaceous have significantly improved the seepage capacity of the reservoir through elastic rebound and pressure reduction expansion mechanisms. Tectonic uplift is the key acquired constructive factor for improving the physical properties of the reservoir in the study area, and the paleotectonic high areas and areas with strong uplift and denudation are the favorable targets for further oil and gas exploration.